Kajian Kritis Peluang dan Tantangan Pendampingan Sertifikasi Halal UMKM: Systematic Literature Review (SLR) - Nijuar, Peri; Handoko, Luqman Hakim; Triyanto, Abdi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study aims to identify trends, opportunities, and challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in the halal certification process, as well as to examine the role of the government and related institutions. This research employs a Systematic Literature Review (SLR) method with a PRISMA-P approach. The data used is secondary data in the form of documents indexed on Google Scholar and Sinta from 2019 to 2024. Data was downloaded using Publish or Perish (PoP) software. The results show a significant increase in publications related to halal certification guidance in 2023 specifically. The opportunities for MSMEs related to halal certification are increased consumer trust, market expansion, and increased product value. 1 However, MSMEs also face challenges such as limited capital, complex procedures, and a lack of information. Therefore, one of the important roles of the government is to issue self-declare regulations for halal certification and the support of the Halal Product Assurance Organizing Body (BPJPH) and Halal Inspection Institution (LPH).